Fermentasi Kitin dari Limbah Cangkang Kepiting Menggunakan Jamur Rhizopus Oryzae pada Berbagai Kadar Air - Retno Dwi Jayanti; Unung Leoanggraini (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Chitin on crab shell waste can be obtained by fermentation process use Rhizopus oryzae. The objective of this research are to determine the optimum of water content on crab shell waste fermentation by Rhizopus oryzae for chitin production. Fermentation process is carried out for 72 hours, 5 of pH, 37oC, and 10% (v/w) of inoculum addition. Water content on fermentation process were varried whithin 40%, 50%, and 60% respectively. Fermentation process were carried out by 40% of water content reported as the optimum based on the deproteinization degree and the solubility in acidic solution.